Pelatihan Pembuatan Produk Herbal sebagai Upaya Pemanfaatan Potensi Lokal Desa Sukalangu Kabupaten Pandeglang - Ucu Wandi Somantri; Candra Junaedi; Fachrudin Perdana; Tarso Rudiana; Nenden Suciyati Sartika; Tuti Rostianti Maulani; Irwan Irwan; Irwanto Irwanto; Ditta Ahmad Herviana; Nur Thooyibah; Widiya Putri; Frida Elasjulia (Lembaga Pengembangan Kinerja Dosen, 2025)
The community service activities carried out in Sukalangu Village, Pandeglang Regency, had the main objective of increasing the utilization of local potential through the development of useful and economic herbal products. The potential of herbal plants in this village is quite abundant, but their utilization is still limited to traditional use for household needs. Therefore, a systematic effort is needed to enable the community to process them into products with added value. The implementation method of the activities included counseling on the benefits of herbal plants for health, technical demonstrations of making simple herbal products such as health drinks and traditional potions, and participatory assistance in the production process. The results of the activities showed a significant increase in community knowledge, with a 40% increase in understanding of the types, benefits, and processing methods of herbs. In addition, technical skills in mixing and processing herbs increased by 50% based on pre- and post-training evaluations. Furthermore, community interest and motivation to develop herbal-based businesses also grew, as demonstrated by the formation of small groups of residents who took the initiative to produce herbal products as household businesses. Other impacts that emerged were increased individual capacity, collective awareness to protect and utilize natural potential, and the opening of sustainable local economic opportunities. Overall, this activity makes a real contribution to supporting the independence of village communities through the utilization of local resources based on traditional wisdom.